Factors Associated with Breast Self-Examination Behavior (BSE) in Young Women - Nurhaya S Patui; Anggi Arum Yudiana; Bertin Ayu Wandira; Ulfa Aulia (Journal of Health and Nutrition Research, 2023)
Breast cancer is the second largest death in women. One of the preventions of breast cancer by early detection is Breast Self-Examination (BSE). It aims at finding out abnormal lumps in the breast. There were 20 cases of breast cancer in Palu in 2017, 10 of them died, then increased in 2018 to 25 cases, and 14 died. Based on preliminary research at Senior High School of SMA 7 Negeri Palu, in 2021, there was 1 case of breast cancer. This research aimed to determine the correlation between knowledge, attitudes, information exposure, parental support, and Breast Self-Examination (BSE) behavior. This was quantitative research with a cross-sectional approach. The samples were taken through the Slovin method with the Proportional Stratified Random Sampling technique. The total population was 396 students, and the total samples were 80 students. The majority of respondents are 17 years old, namely 52.5% with good behavior, namely 52.5%, knowledge including lack, namely 55%, attitude including negative, namely 60%, and information exposure including high, namely 56.2%, and parental support including lack, namely 51.2%. The results show that there was no correlation between information exposure and BSE behavior (p = 0.128), while knowledge (p = 0.022), attitudes (p = 0.001), and parental support (p = 0.003) showed a correlation with BSE behavior. It is expected that the school will cooperate with the health sector by providing material on reproductive health and prevention of non-communicable diseases, and the students are also more proactive in seeking information related to BSE